Original researchRisk factors in Central Poland for the development of superficial and nodular basal cell carcinomas - Lesiak, Aleksandra; Slowik-Rylska, Malgorzata; Rogowski-Tylman, Michal; Norval, Mary; Narbutt, Joanna (Archives of Medical Science, 2010)
Introduction: In the last decades the number of skin carcinomas has dramatically increased, which is mainly connected with changes in lifestyle, especially with common use of artificial light sources such as sunbeds. Basal cell carcinoma (BCC) is the most common form of skin cancer in white populations. Basal cell carcinomas are divided into subtypes, depending on their clinical picture and histology. The main groups are nodular (nBCC) and superficial (sBCC) ones. The major recognized risk factors for basal cell carcinoma (BCC) are exposure to chronic and intermittent burning doses of sunlight. Other risk factors leading to the development of the nBCC and sBCC subtypes of BCC are not well established. Material and methods: An analysis of 123 patients with either nBCC or sBCC, living in Lodz, Poland, regarding various intrinsic and environmental parameters was undertaken following the histological diagnosis of BCC. Results: No statistical differences were observed between the BCC subtype and sex, age, hair colour, eye colour, smoking, family history of skin cancer, occupation, or past episodes of sunburn. While sBCCs tended to occur on unexposed body sites in phototype I/II subjects who mainly avoided direct sunlight, nBCCs tended to occur on sun-exposed body sites in phototype III subjects who were frequently in direct sunlight. Conclusions: Thus the development of particular BCC subtypes is partially dependent on phototype and personal sun behaviour.